2010
DOI: 10.1111/j.1365-2591.2010.01828.x
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of nonthermal atmospheric pressure plasma for intracoronal bleaching

Abstract: The application of nonthermal atmospheric pressure plasma to intracoronal bleaching could be a novel and efficient therapy in the bleaching of haemorrhagically stained teeth.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
46
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 64 publications
(51 citation statements)
references
References 22 publications
3
46
0
2
Order By: Relevance
“…For example, the energies needed to break an HO-OH bond and an HO 2 -H bond are 2.2 eV and 3.8 eV, respectively, for the formation of the reactive OH radical used as the main species in applications such as tooth bleaching, sterilization, and metal-surface treatment. [25][26][27][28] Furthermore, energetic electrons are a likely another major source of damage to DNA molecules for biomedical applications such as cancer treatment and bacterial inactivation because electrons with Here, s p is the pulse period (s p ¼ 100s rf ) and n is integer (n 1) representing the number of pulse period. sufficient energy can induce DNA SSB and DSB.…”
Section: Resultsmentioning
confidence: 99%
“…For example, the energies needed to break an HO-OH bond and an HO 2 -H bond are 2.2 eV and 3.8 eV, respectively, for the formation of the reactive OH radical used as the main species in applications such as tooth bleaching, sterilization, and metal-surface treatment. [25][26][27][28] Furthermore, energetic electrons are a likely another major source of damage to DNA molecules for biomedical applications such as cancer treatment and bacterial inactivation because electrons with Here, s p is the pulse period (s p ¼ 100s rf ) and n is integer (n 1) representing the number of pulse period. sufficient energy can induce DNA SSB and DSB.…”
Section: Resultsmentioning
confidence: 99%
“…Other similar studies by Dong X et al and Ritts AC et al also revealed that plasma treatment improved the interfacial bonding strength 22,23 .…”
Section: Applications Of Cold Plasma In Conservative Dentistrymentioning
confidence: 63%
“…Preliminary reports of a new method called low-temperature atmospheric pressure plasma (ltAPP) indicated effective results in disinfection and sterilization, biofilm removal and intracoronal bleaching (14,30). Furthermore, surface treatment using ltAPP was encouraging in the surface and tissue engineering, cleaning/etching, adhesion enhancement, and biomaterial development (5,17).…”
Section: Introductionmentioning
confidence: 99%